Structuring and functionalization of non-metallic materials using direct laser interference patterning: A review - Mulko, Lucinda (2021)
Direct laser interference patterning (DLIP) is a laser-based surface structuring method that stands out for its high throughput, flexibility and resolution for laboratory and industrial manufacturing. This top-down technique relies on the formation of an interference pattern by overlapping multiple laser beams onto the sample surface and thus producing a periodic texture by melting and/or ablating the material. Driven by the large industrial sectors, DLIP has been extensively used in the last decades to functionalize metallic surfaces, such as steel, aluminium, copper or nickel. Even so, DLIP processing of non-metallic materials has been gaining popularity in promising fields such as photonics, optoelectronics, nanotechnology and biomedicine. This review aims to comprehensively collect the main findings of DLIP structuring of polymers, ceramics, composites, semiconductors and other non-metals and outline their most relevant results. This contribution also presents the mechanisms by which laser radiation interacts with non-metallic materials in the DLIP process and summarizes the developed surface functions and their applications in different fields.